2016
DOI: 10.1097/ico.0000000000000869
|View full text |Cite
|
Sign up to set email alerts
|

Report of the Eye Bank Association of America Medical Review Subcommittee on Adverse Reactions Reported From 2007 to 2014

Abstract: PGF was the most commonly reported adverse reaction, disproportionately associated with EK. An increasingtrend in the rate of endophthalmitis and keratitis was observed, disproportionately associated with EK and Candida species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
72
1
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(80 citation statements)
references
References 21 publications
(36 reference statements)
5
72
1
2
Order By: Relevance
“…This can be explained by long learning curves required for DSAEK and DMEK. Similar to the report by the EBAA between 2007 and 2014, [45] primary GF predominated in our series over the last 12 years. Different from the EBAA report in which Candida species was the most frequent isolated pathogen in post-corneal graft endophthalmitis, [45] Gram-positive microorganisms predominated in our series.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This can be explained by long learning curves required for DSAEK and DMEK. Similar to the report by the EBAA between 2007 and 2014, [45] primary GF predominated in our series over the last 12 years. Different from the EBAA report in which Candida species was the most frequent isolated pathogen in post-corneal graft endophthalmitis, [45] Gram-positive microorganisms predominated in our series.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to the report by the EBAA between 2007 and 2014, [45] primary GF predominated in our series over the last 12 years. Different from the EBAA report in which Candida species was the most frequent isolated pathogen in post-corneal graft endophthalmitis, [45] Gram-positive microorganisms predominated in our series. Regarding infectious keratitis, no significant difference was found between the rate of fungal keratitis and keratitis caused by Gram-negative bacteria in our survey; this result is different from that of the EBAA report.…”
Section: Discussionsupporting
confidence: 92%
“…Keratitis postcorneal transplant is most commonly due to Candida spp (80% of cases). This is due in part to the most widely used corneal holding medium not containing any antifungal agents [55]. A corneal swab specimen is used to inoculate an agar plate containing nonnutritive medium at the patient's bedside and then transported immediately to the laboratory.…”
Section: E Keratitismentioning
confidence: 99%
“…202 Along with the popularity of EK came an increase in case reports of fungal infections, prompting large database studies that confirmed its rise. [203][204][205] Although rare, the incidence of postkeratoplasty fungal infections (most commonly Candida species) has grown in recent years from 0.014% in a 2013 report 203 to 0.023% in a 2016 report. 204 The additional warming period required for EK processing has been found to be a factor in fungal infections.…”
Section: Intraoperativementioning
confidence: 99%
“…[203][204][205] Although rare, the incidence of postkeratoplasty fungal infections (most commonly Candida species) has grown in recent years from 0.014% in a 2013 report 203 to 0.023% in a 2016 report. 204 The additional warming period required for EK processing has been found to be a factor in fungal infections. 206 In contrast to the discordance of positive bacterial culture donor rims to clinical infection, multiple studies show positive fungal culture donor rims to have predictive value.…”
Section: Intraoperativementioning
confidence: 99%